A low noise front end electronics for micro-channel plate detector with wedge and strip anode. (15th March 2016) - Hu, K.; Li, F.; Liang, F.; Chen, L.; Jin, G.
Abstract: A low noise Front End Electronics (FEE) for two-dimensional position sensitive Micro-Channel Plate (MCP) detector has been developed. The MCP detector is based on Wedge and Strip Anode (WSA) with induction readout mode. The WSA has three electrodes, the wedge electrode, the strip electrode, and the zigzag electrode. Then, three readout channels are designed in the Printed Circuit Board (PCB). The FEE is calibrated by a pulse generator from Agilent. We also give an analysis of the charge loss from the CSA. The noise levels of the three channels are less than 1 fC RMS at the shaping time of 200 ns. The experimental result shows that the position resolution of the MCP detector coupled with the designed PCB can reach up to 110 μ m.